THE ROLE OF INDUSTRIAL ROBOTS IN MECHANICAL ENGINEERING AND WAYS TO CREATE SOFTWARE FOR ROBOTS - Abdulatif Abdubannopov; Sukhrobbek Muydinov (Western European Studies, 2024)
This article explores the current landscape of industrial robotics and the concurrent development of software tailored for these systems. Recognizing the increasing relevance of industrial robots and their associated software, the discussion highlights their significant footprint in various sectors. As information and communication technologies rapidly advance, the article observes a compelling trajectory towards a future where personalized intelligent robots become commonplace. The exploration of this evolving landscape contributes to a deeper understanding of the integral role industrial robots and their software counterparts play in shaping our technological future
Keywords: Robot; industry; enterprise